ANALISIS BEBAN KERJA PT. X - Nina Dannies; Verina Halim; Heru Haryanto (CALYPTRA, 2015)
Every company wants optimal productivity. One of the ways is to have workload analysis to balance number of employees to workload allocations. Early result survey shows that less employees causes bigger workload, which impact on less productivity. Thus conclude the need of workload analysis to get the right number of employees, so the company can have optimal productivity. Assessment result shows existence of 3 work units that need changes on number of employees. The intervention design which proposed is job design. Suggestion to the company is consideration on team of work movement and ergonomic values, also workload analysis on other department. Setiap perusahaan menginginkan produktivitas kerja yang optimal. Salah satu cara yang dapat dilakukan adalah dengan melakukan analisis beban kerja untuk menyeimbangkan jumlah karyawan dengan alokasi beban kerja. Hasil survey awal menunjukkan bahwa pengurangan jumlah karyawan menyebabkan beban kerja yang semakin meningkat, dan berdampak pada penurunan produktivitas kerja. Hasil asesmen menunjukkan adanya 3 unit kerja yang membutuhkan perubahan jumlah pegawai. Rancangan intervensi yang diusulkan adalah job design. Saran bagi perusahaan adalah pertimbangan dari segi gerakan kerja dan nilai-nilai ergonomis, serta analisis beban kerja pada departemen lain.